Pengaruh Inflasi Terhadap Keuangan Bank Syariah di Indonesia Tahun 2019-2023 - Anggel Jenita Devi; M. Zidny Nafi’ Hasbi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Islamic banks are financial institutions that operate in accordance with Islamic law and do not charge interest to their customers. Contracts and agreements between consumers and banks determine the profit-sharing (inbalam) received by Islamic banks and those received by customers. The purpose of this study is to determine the effect of inflation on Islamic bank finance in Indonesia from 2019 to 2023. The research method employed is a quantitative approach. The data source utilized is the Financial Services Authority (OJK), with document data collection techniques. Data analysis in this study involves simple linear regression analysis, t-test, F-test, and coefficient of determination (R²) test. The results indicate that inflation has no effect on the profitability of Islamic banking in Indonesia during the period from 2019 to 2023. This conclusion is drawn because the t-test results yielded a t-value of 1.359 < t-table 2.01505 and a significance value of 0.267 > 0.05, indicating no influence between the independent variable (inflation) and the dependent variable (profitability). Therefore, it can be concluded that inflation does not have a partial and significant effect on Islamic banking profitability in Indonesia during the 2019–2023 period.